THE EFFECT OF BAY LEAF (SYZYGIUM POLYANTHUM) DECOCTION ON SYSTOLIC BLOOD PRESSURE REDUCTION AMONG HYPERTENSIVE PATIENTS - Rapika, Nor; Tasalim, Rian (HEARTY, 2026)
Hypertension is a major global public health concern and one of the leading causes of cardiovascular morbidity and mortality. In Indonesia, its prevalence continues to rise, particularly among adults in primary healthcare settings. Complementary and alternative treatments using natural ingredients have gained attention for their accessibility, affordability, and cultural acceptance. Bay leaf (Syzygium polyanthum) is a traditional Indonesian medicinal plant containing flavonoids, tannins, and alkaloids, which have vasodilatory and diuretic properties. This study aimed to analyze the effect of bay leaf decoction on systolic blood pressure reduction among hypertensive patients at the Gambut Health Center. A pre-experimental design with a one-group pretest–posttest approach was applied involving 15 hypertensive patients selected through purposive sampling. Participants consumed 200 ml of bay leaf decoction once daily for seven consecutive days. Blood pressure was measured before and after the intervention using a digital sphygmomanometer, and data were analyzed using a paired sample t-test. The results showed a significant decrease in mean systolic blood pressure from 156.53 ± 12.48 mmHg to 136.00 ± 10.23 mmHg (p = 0.000061). This finding demonstrates that bay leaf decoction effectively lowers systolic blood pressure among hypertensive patients. In conclusion, bay leaf decoction can be recommended as a safe, affordable, and culturally accepted complementary therapy for managing hypertension in primary healthcare settings.